Vitamin C and Metabolic Syndrome: A Meta-Analysis of Observational Studies - Guo, Hongbin; Ding, Jun; Liu, Qi; Li, Yusheng; Liang, Jieyu; Zhang, Yi (Frontiers in Nutrition, 2021)
Abstract Background: The association between vitamin C and metabolic syndrome (MetS) has been evaluated in several epidemiological studies with conflicting results. This meta-analysis was therefore employed to further investigate the above issue. Methods: The observational studies on the associations of dietary and circulating (serum and plasma) vitamin C level with MetS were searched in the PubMed, Web of Science and Embase database up to April 2021. The pooled relative risk (RR) of MetS for the highest versus lowest dietary and circulating vitamin C level, and the standard mean difference (SMD) of dietary and circulating vitamin C level for MetS versus control subjects were calculated, respectively. Results: A total of 28 observational studies were identified in this meta-analysis. Specifically, 23 studies were related to the dietary vitamin C level. The overall multi-variable adjusted RR demonstrated that the dietary vitamin C level was inversely associated with MetS (RR=0.93, 95%CI: 0.88 to 0.97; P=0.003). Moreover, the overall combined SMD showed that the dietary vitamin C level in MetS was lower than that in control subjects (SMD=-0.04, 95%CI: -0.08 to -0.01; P=0.024). With regard to the circulating vitamin C level, 11 studies were included. The overall multi-variable adjusted RR demonstrated that the circulating vitamin C level was inversely associated with MetS (RR=0.60, 95%CI: 0.49 to 0.74; P<0.001). In addition, the overall combined SMD showed that the circulating vitamin C level in MetS was lower than that in control subjects (SMD=-0.82, 95%CI: -1.24 to -0.40; P<0.001). Conclusions: Current evidence suggests that both dietary and circulating vitamin C level is inversely associated with MetS. However, due to the limitation of available evidence, more well-designed prospective studies are still needed. Keywords: Dietary vitamin C, Circulating vitamin C, Metabolic syndrome, Meta-analysis, Observational studies